Bellidifolin Ameliorates Isoprenaline-Induced Myocardial Fibrosis by Regulating TGF-β1/Smads and p38 Signaling and Preventing NR4A1 Cytoplasmic Localization - Yang, Hong-Xia; Sun, Jia-Huan; Yao, Ting-Ting; Li, Yuan; Xu, Geng-Rui; Zhang, Chuang; Liu, Xing-Chao; Zhou, Wei-Wei; Song, Qiu-Hang; Zhang, Yue; Li, Ai-Ying (Frontiers in Pharmacology, 2021)
Myocardial fibrosis is closely related to high morbidity and mortality. In the Inner Mongolian, Gentianella amarella subsp. acuta (Michx.) J.M.Gillett (G. acuta) is a kind of tea used to prevent cardiovascular diseases. Bellidifolin (BEL) is an active xanthone molecule from G. acuta that protects against myocardial damage. However, the effect and mechanism of BEL on myocardial fibrosis have not been reported. In vivo, BEL dampened isoprenaline (ISO)-induced cardiac structure disturbance, and collagen deposition. In vitro, BEL inhibited transforming growth factor (TGF)-β1-induced cardiac fibroblast (CF) proliferation. In vivo and in vitro, BEL decreased the expression of α-smooth muscle actin (α-SMA), collagen Ⅰ and Ⅲ, and inhibited TGF-β1/Smads signaling. Additionally, BEL impeded p38 activation and NR4A1 (an endogenous inhibitor for pro-fibrogenic activities of TGF-β1) phosphorylation and inactivation in vitro. In CFs, inhibition of p38 by SB203580 inhibited the phosphorylation of NR4A1, and didn't limit Smad3 phosphorylation. And blocking TGF-β signaling by LY2157299 and SB203580 could decrease the expression of α-SMA, collagen I and III. Overall, both cell and animal studies provide a potential role for BEL against myocardial fibrosis by inhibiting the proliferation and phenotypic transformation of CFs. These inhibitory effects might be related to regulating TGF-β1/Smads pathway and p38 signaling and preventing NR4A1 cytoplasmic localization.